Competition and innovation: An experimental investigation - Dario Sacco (University of Zurich, Socioeconomic Institute, 2007)
The paper analyzes the effects of competitive intensity on firms' incentives to invest in process innovations through an experiment based on two-stage games, where R&D investment choices are followed by product market competition. An increase in the intensity of competition is modeled as an increase in the number of þrms or as a switch from Cournot to Bertrand. The theoretical prediction is that more intense competition is unfavorable to investments for both cases. In the experiment it turns out that the way of modeling the intensity of competition is essential. The theoretical prediction is confirmed for the number effects. On the other hand, the comparison of Cournot and Bertrand shows that more intense competition is beneþcial for investments.
Keywords: C92; L13; O31; 330; R&D investment; intensity of competition; experiment; Innovation; Investition; Wettbewerbsstrategie; Test